Real‐world treatment practice in patients with advanced melanoma in the era before ipilimumab: results from the IMAGE study. (26th April 2016) - Middleton, Mark R.; Dalle, Stéphane; Claveau, Joel; Mut, Pilar; Hallmeyer, Sigrun; Plantin, Patrice; Highley, Martin; Kotapati, Srividya; Le, Trong Kim; Brokaw, Jane; Abernethy, Amy P.
Abstract: The therapeutic landscape for advanced melanoma has recently been transformed by several novel agents (immune checkpoint inhibitors and molecular‐targeted agents). The prospective, multi‐site, observational study IMAGE (ipilim umab: manage ment of advanced melanoma in real practice) included a retrospective cohort to describe real‐world treatment prior to approval of the immune checkpoint inhibitor ipilimumab. This retrospective cohort of patients, who started second‐line/subsequent treatment (index therapy) for advanced melanoma within 3 years before ipilimumab approval, was selected randomly by chart review. Collected data included treatment history, patient outcomes, and healthcare resource utilization. All patients had ≥1 year of follow‐up data. This analysis included 177 patients from Europe (69%) and North America (31%). The most common index therapies (used alone or in combination) were fotemustine (23%), dacarbazine (21%), temozolomide (14%), and platinum‐based chemotherapy (14%). Most patients (89%) discontinued index treatment during the study period; the most common reason was disease progression (59%). Among patients with tumor assessment (153/177; 86%), 2% had complete response, 5% had partial response, and 12% had stable disease on last tumor assessment. At 1‐year study follow‐up, median progression‐free survival was 2.6 months (95% confidence interval [CI], 2.1–2.9) and median overall survival was 8.8 months (95% CI, 6.5–9.7). During follow‐up, 95% of the patients had healthcare visits for advanced melanoma, 74% of whom were hospitalized or admitted to a hospice facility. These results provide insights into patient care with advanced melanoma in the era before ipilimumab and may serve as a benchmark for new agents in future real‐world studies. Abstract : The IMAGE (ipilimumab: management of advanced melanoma in real practice; ClinicalTrials.gov Identifier: NCT01511913) study is a multi‐site, observational study evaluating real‐world treatment and patient outcomes for advanced melanoma, both prospectively and retrospectively. Results from the retrospective cohort, which was treated in the era before the immuno‐oncology agent ipilimumab, confirm the previous unmet need in advanced melanoma and provide historical information to facilitate the assessment of recent treatment patterns and trends in advanced melanoma.